2023
DOI: 10.1007/s12035-023-03415-7
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Amygdala Reveals Dynamic Changes in Glutamate Transporter-1 During Progression of Complete Freund’s Adjuvant-Induced Pain Aversion

Abstract: Pain sufferer usually show an aversion to the environment associated with pain, identified as pain aversion. The amygdala, an almond-shaped limbic structure in the medial temporal lobe, exerts a critical effect on emotion and pain formation. However, studies on inflammatory pain-induced aversion are still relatively limited, and the available evidence is not enough to clarify its inherent mechanisms. Proteomics is a high-throughput, comprehensive, and objective study method that compares the similarities and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…This region collaborates with other brain regions to form a complex neural network that is foundational to higher cognitive functions in humans. Studies have shown that temporal lobe involvement is associated with unpleasant emotions (41)(42)(43) and that the temporal lobe is primarily responsible for pain perception and emotional processing (5,44,45). Presently, researchers are observing structural and functional changes in this region in a variety of pain-related disorders (46)(47)(48)(49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…This region collaborates with other brain regions to form a complex neural network that is foundational to higher cognitive functions in humans. Studies have shown that temporal lobe involvement is associated with unpleasant emotions (41)(42)(43) and that the temporal lobe is primarily responsible for pain perception and emotional processing (5,44,45). Presently, researchers are observing structural and functional changes in this region in a variety of pain-related disorders (46)(47)(48)(49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%